Development of Tools Growth Catfish Based on the Internet of Things (IoT) - Ahmad Minanur Rohim; Edy Cahyono; Retno Sri Iswari (Faculty of Science and Education, UIN Walisongo Semarang, 2022)
Factors that affect the growth of catfish include water temperature, pH levels, and feeding according to the growth of catfish. Feeding and water replacement are currently still done manually, using human power. Maintaining feed and water quality in the tub automatically is necessary to save time and effort. The automatic settings to maintain feed and water temperature as well as good water acidity for catfish in the tub can use the NodeMCU microcontroller. This research method is carried out by designing tools, testing tools, objects and stages of tools and concluding. Parameters of water temperature and pH levels of water are sent to the telegram application, as well as to regulate the discharge of water, a pump that works automatically is used through a relay that is installed automatically. The monitoring results are successfully displayed via the ThingViewer application. The tool has worked well with tests carried out including testing the design of the tool, testing the temperature sensor, testing the pH sensor, and testing the sending of orders from Telegram. The yields obtained were different between the two treatments, namely without using tools (non-tools) using tools (tools), the ideal growth of catfish for a temperature of 29 °C and a minimum pH of 6.5 and a maximum of 9.